The conscientious justice : how Supreme Court justices' personalities influence the law, the high court, and the Constitution / Ryan C. Black, Ryan J. Owens, Justin Wedeking, Patrick C. Wohlfarth. - Black, Ryan C., 1982-; Owens, Ryan J., 1976-; Wedeking, Justin; Wohlfarth, Patrick C. (Cambridge University Press, 2020)
United States Supreme Court justices make decisions that have a profound impact on American society. Empirical legal scholars have portrayed justices as either single-minded or strategic seekers of policy, and there is little room in these theories for things like law, reputation, or personality. This book offers a fresh perspective that will jar Supreme Court scholarship out of complacency. It argues that justices' personalities influence their behavior, which in turn influences legal development and the United States Constitution. This impressive group of authors exhaustively examine every part of the Court's decision-making process, and focus on the trait of conscientiousness and how it influences justices over nine different empirical contexts, from agenda setting to writing the Court's opinions. The Conscientious Justice is an important and comprehensive account of judging that restructures existing approaches to analyzing the High Court.